The Sexuality of Authorship in The Monk - Fitzgerald, Lauren (Romanticism on the Net)

(untitled) (Université de Montréal, 2004)
AbstractAs simultaneously “queer” and “unoriginal,” the Gothic is an ideal site for investigating alternatives to the still potent Romantic construction of the author as masculine, heterosexual, and autonomous. One of the best examples of this Gothic alternative is the original queer Gothic plagiarist, Matthew Lewis. Drawing on Judith Butler’s insight that drag—and by implication gender—is a form of imitation that calls into question the “originality” of any normatively delineated gender identity, this essay examines the authorship of The Monk by way of a usually overlooked episode in which Lewis situates himself in a classical, imitative, and homoerotic literary tradition and echoes his famous avowal of the romance’s “plagiarisms.” Like the crafty cross-dresser Rosario/Matilda, Lewis’s authorship lacks stable ground. More important, by circumventing the primacy of origins, he claims a legacy that queers the history of the sexuality of authorship.